Valuation of Synedrella nodiflora leaves in rabbit feeding as feed supplement: impact on reproductive performance - KOUTINHOUIN, G. BENOÎT; TOUGAN, P. ULBAD; KPODEKON, TCHOKPONHOUE TCHEGNINOUGBO MARC; BOKO, KADOÉITO CYRILLE; GOUDJIHOUNDE, MARTIN; AOULOU, ABEL; Thewis, André (My University, 2014)
The current study aims to evaluate the effect of Synedrellanodiflora leaves used as feed supplement in the diet of rabbits on their reproductive performances. Then, 96 rabbits (80 primiparous females and 16 males)of Common breed were divided into 4 lots and subjected to different dietary treatments. In lot1, only the female rabbits had received Synedrellanodiflora leaves. In lot 2, both males and females were all fed with Synedrellanodiflora. In lot 3, only the males were fed Synedrellanodiflora, while in lot 4 (control group) neither males nor females were fed with Synedrellanodiflora. It appears that the highest litter size (P˂0.001) was recorded in lot 1 and lot 2. At weaning, the highest litter size was recorded in lot 2 (P˂0.001). The live weight at 25 and 35 days old in kits of lots 3 and lot 4 were higher than those recorded in lots 1 and 2 (P˂0.001). The fertility rateof lot 3 was 100% to 80%, 89% and 70% respectively for lot 1, 2 and 4 (P˂0.001). The kidding rate was 100% in lots 1, 2 and 4 to 88% in lot 3. Similarly, the highest stillbirth rate was recorded in lot 3 (P˂0.001). Synedrellanodifloraleaveshad reduced the mortality rate from the birth to the weaning from 14% to 3.4% with the highest rate observed in the control group (P˂0.001).Overall, Synedrellanodiflora leaves using as feed supplement in rabbits improves fertility rate and litter size, and reduces significantly the mortality rate from birth to weaning.
Keywords: Benin; growth; rabbit does; reproductive performance; Synedrellanodiflora